How Gintong Alay Won Gold: Policy Evaluation of the Elite Sport Flagship Project under the Marcos Administration, 1978-1981 - Perez, Micah Jeiel (Archīum Ateneo, 2021)
This study made use of the SPLISS (Sport Policy Factors that Lead to International Sporting Success) framework by De Bosscher, et. al. to help determine the key policy factors behind the international medal success of Project: Gintong Alay, the national elite sport development (ESD) program under the Marcos administration. The study focuses elements of elite sports influenced by national policies from the program’s establishment in 1979 up to its first real test in the 1981 Manila SEA Games. Using data from the sports pages of three major newspapers at the time— Bulletin Today, the Philippine Daily Express, and the Times Journal—feature articles in WHO and Philippine Panorama magazines, and various presidential documents (e.g. Executive Orders, Letters of Instruction, Presidential Decrees, etc.), it was concluded that most of Gintong Alay’s medal success can be attributed to three (3) critical factors: 1) the efficient use of resources through the prioritization of sports with a high possibility of medal returns, 2) the creation of an athlete-centric model for national team training, and 3) the continuous exposure of elite athletes to high levels of international competition. It was also concluded that Gintong Alay succeeded despite failing to achieve some of the SPLISS model’s key success factors because of its unique historical context, that being a sports program under an authoritarian regime known for its crony capitalism and love for propaganda/image building.